2017
DOI: 10.21699/ajcr.v8i3.568
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoschisis associated with Limb Body Wall Complex

Abstract: Thoracoschisis is a rare condition. A female newborn presented with right-sided thoracoschisis, associated with diaphragmatic hernia and protrusion of an accessory liver lobe through the chest wall defect along with deformity of the right forearm and hand duplication. Diagnosed as part of the limb-body wall complex (LBWC), management included resection of the exteriorized liver lobe followed by right hemidiaphragm and thoracic wall reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…4), rather than fitting completely into one of the traditional diagnostic silos, instead span across more than one of these diagnoses. 31,42,[45][46][47][48] In our own cohort, six of the seven complicated VBWD cases encountered over a 24-month period demonstrated just such a hybrid constellation of findings. The traditional diagnostic categories may obscure more than they reveal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), rather than fitting completely into one of the traditional diagnostic silos, instead span across more than one of these diagnoses. 31,42,[45][46][47][48] In our own cohort, six of the seven complicated VBWD cases encountered over a 24-month period demonstrated just such a hybrid constellation of findings. The traditional diagnostic categories may obscure more than they reveal.…”
Section: Discussionmentioning
confidence: 99%
“…No craniofacial defects but abdominal-placental attachment with short/absent umbilical cord and urogenital anomalies 35 Body stalk anomaly Large abdominal wall defect with herniation of abdominal contents into the extraembryonic coelom Absent or rudimentary umbilical cord 34 Proposed common findings Absent/rudimentary/short umbilical cord 32,34,47,58 Limb anomalies Pseudosyndactyly without amniotic bands, oligodactyly, polydactyly, split hand and foot, single bone forelimb, forebone abnormalities, absent limb and limb girdle, absent muscles and arthrogryposis 7,63 Clubbed feet, single lower limb 34 Bilateral clubbed feet 32 Club foot, rocker bottom foot 47 Neural tube defects 46,58 Exencephaly or encephalocele 7,63 Abdominal wall defects Abdominoschisis 34,64 Omphalocele 32,39,47 Skeletal abnormalities Kyphoscoliosis 32,34 Scoliosis 46,47,64 Craniofacial abnormalities 28,34 Case reports Encephalocele, anophthalmia, bilateral cleft lip, thoracic cleft with ectopia cordis, omphalocele, short umbilical cord, single umbilical artery 39 Ectopia cordis 11…”
Section: Craniofacial Defects Often With Cranioplacental Adhesion Andmentioning
confidence: 99%
“…The phenotype in the ABS classified cases was 11 abdominal, five cranial, three CR/AB overlapped phenotype, one CR/SPDYS, and two ABS cases did not show specific phenotype. All cases classified in this study as ABS were considered as LBWC in their original report (Gajzer et al, case 3;Kamudhamas & Manusook, 2001 case 1; Kruszka et al, 2015 cases: 1 and 2; Moerman et al, 1992 cases: 11-13;Sahinoglu et al, 2007 case 5;Vujovic et al, 2017), or as LBWD (Gazolla et al, 2014 cases 1 and 6), except for cases 1, 2, and 9 which were reported as ABS by Routhu et al (2016).Case 3 reported as LBWC by Gajzer, Hirzel, Saigal, Rojas, and Rodriguez (2015) showed gastroschisis, normal UC, spinal anomaly, and clubfoot, thus it was not classified as BSA or LBWC. Gastroschisis is a full-thickness abdominal wall occurring lateral to the UC, and, in most cases, is an isolated anomaly, but sometimes may occur in combination with other congenital anomalies as arthrogryposisin the hindlimbs (Martín-Alguacil & Avedillo, 2020b).…”
Section: Martín-alguacilmentioning
confidence: 99%
“…Diagnosis of the full extent of the defect differs on a case-by-case basis, but usually involves chest radiography (CXR) or computed tomography (CT) scans [4]. Exploratory operations are often necessary as it is sometimes unclear whether there is an elevated hemidiaphragm or a diaphragmatic hernia [8,10].…”
Section: Introductionmentioning
confidence: 99%